Inherited sterility in Tuta absoluta (Lepidoptera: Gelechiidae): Pest population suppression and potential for combined use with a generalist predator - Cagnotti, Cynthia Lorena (2016)
Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae) is one of the most devastating pests of tomato. We studied whether partially sterile T. absoluta males and fully sterile females were capable of suppressing wild populations of this moth in semi-controlled conditions. After irradiating T. absoluta pupae with 200 Gy, emerged males and females were released at 10:1 (treated:untreated) and 15:1 over-flooding ratios inside field cages containing tomato plants. The number of eggs and larvae produced was recorded once per wk during 3 mo. An over-flooding ratio of 10:1 caused a decline in larvae production compared with the untreated control cages, but these differences were not statistically significant. Using an over-flooding ratio of 15:1, the moth population in the cages with irradiated insects decreased significantly compared with those in the untreated control cages. In addition, the possibility of combining inherited sterility and a natural enemy as a strategy to manage this pest was investigated. We studied in no choice and choice tests the predation behavior of females of the egg predator Tupiocoris cucurbitaceus (Hemiptera: Miridae) on eggs derived from the following parental T. absoluta crosses: U × U (control), U × I and I × U (where U = untreated, I = irradiated). In the no choice test, females of the T. cucurbitaceus readily consumed T. absoluta eggs regardless of their origin. In the choice test, T. cucurbitaceus females consumed similar numbers of eggs of untreated parents and eggs oviposited from crosses in which the male had been irradiated. However, the mirid females preyed on significantly more eggs—roughly 20% more—from irradiated females than on eggs from untreated females. We conclude that it is possible to achieve a certain level of suppression of a T. absoluta wild population through the release of irradiated insects, and that it is technically feasible to combine the use of the predator T. cucurbitaceus with inherited sterility to control this moth pest.